MS-150-10-f02-001: Letter from Julia Peal, April 17, [between 1884-1895] - Peal, Julia (Valdosta, GA: Valdosta State University Archives and Special Collections, 1884)
Letter from Julia Peal, April 17, [between 1884-1895]. Written on Speaker of the House of Commons stationery.
1 handwritten letter, 4 pages.
Keywords: Personal correspondence; Arnold, Edwin, Sir, 1832-1904; Letters; Poets--Correspondence